A CAUSAL RELATIONSHIP OF FACTORS INFLUENCING LEARNING ACHIEVEMENT OF MATHAYOMSUKSA 6TH STUDENTS UNDER SECONDARY EDUCATIONAL SERVICE AREA OFFICE 4 - Aggavaddhano (Nookua), Phra Nattawut; Thitavaddhano, Phramaha Yannawat; Klomkul, Lampong (Journal of Educational Review Faculty of Education in MCU, 2022)
This research article aimed to study the causal relationship of factors influencing learning achievement of Mathayomsuksa 6th students in secondary schools under Secondary Educational Service Area Office 4. Qualitative research method was designed and collected data from 12 key informants who were Mathayomsuksa 6th teachers who had teaching experience not less than 10 years, received senior professional level teachers, and being a recognized teacher.Data was analyzed by content analysis. Results showed that a causal relationship of factors influencing learning achievement of Mathayomsuksa 6th students in secondary schools under Secondary Educational Service Area Office 4 consisted of variables 1) teaching quality, 2) characteristics of friends, 3) family environment, 4) characteristics of students, 5) Trisikkha, and 6) learning achievement.